94 A study of psychogenic non-epileptic seizures in children and adolescents; characteristics and experiences of a case series. (4th October 2017) - McWilliams, A; Reilly, C; McFarlane, F; Heyman, I
Abstract : Background: Non-Epileptic Seziures (NES) involve alterations in behaviour or consciousness that resemble epileptic seizures but are not accompanied by electrophysiological changes. Understanding of NES is underdeveloped in young people. The aim of this study was to develop understanding of patient, family and clinician experiences of non-epileptic seizures (NES) and describe patient characteristics. Methods: A mixed methods approach was used: Focus groups and telephone interviews (10 patients, 29 family members) exploring the impact of living with NES and experiences of health services. Data were analysed using thematic analysis. Case note analysis (n=29): risk factors, co-morbidity, features of presentations, investigations and management. Questionnaires to elicit further opinions from patients, families and clinicians. Results: Participants described confusion and frustration when accessing healthcare. Families felt that the diagnosis of NES was given lower status than that of epilepsy, especially in non-specialist and emergency settings, and had concerns that fits were sometimes regarded as "faked". Patients often could identify the stressors which caused a seizure, but described a loss of freedom with schools seeming to struggle to support them. The preferred name was "non-epileptic seizures" (64%). Clinicians described a wide range of approaches to management, including cognitive-behavioural therapy. Features of cases include: patient sex (female 62.1%), ethnicity (white British 69.0%), co-morbidity of epilepsy (31.0%), psychiatric co-morbidity (depression 24.1%; anxiety 24.1%), co-morbid other medically unexplained symptoms (51.7%), siblings with epilepsy or febrile convulsions (17.2%), age of NES onset (mean 12.4 y, minimum 5.5 y), length of time to diagnosis (mean 1.7 y). Of 15 patients without co-morbid epilepsy, 46.7% had received emergency "rescue" medication for epilepsy. Conclusions: Arriving at a diagnosis can be a long and arduous journey, with non-specialist professionals poorly trained to help. Better integration of paediatric and mental health care is key to improving pathways and access to treatment.